Sigma-1 receptor and seizures - Edijs Vavers; Liga Zvejniece; Maija Dambrova (Elsevier, 2023)
Over the last decade, sigma-1 receptor (Sig1R) has been recognized as a valid target for the treatment of seizure disorders and seizure-related comorbidities. Clinical trials with Sig1R ligands are underway testing therapies for the treatment of drug-resistant seizures, developmental and epileptic encephalopathies, and photosensitive epilepsy. However, the direct molecular mechanism by which Sig1R modulates seizures and the balance between excitatory and inhibitory pathways has not been fully elucidated. This review article aims to summarize existing knowledge of Sig1R and its involvement in seizures by focusing on the evidence obtained from Sig1R knockout animals and the anti-seizure effects of Sig1R ligands. In addition, this review article includes a discussion of the advantages and disadvantages of the use of existing compounds and describes the challenges and future perspectives on the use of Sig1R as a target for the treatment of seizure disorders.